Firm Life Cycle and Cash Policy - Pratana Puspa Midiastuty; Eddy Suranta; Rini Indriani; Anton Robiansyah (Dinasti International Journal of Economics, Finance & Accounting, 2023)
This study aims to examine how the stages of the company's life cycle affect the company's cash policy. This study focuses on the stages of the firm's life cycle which includes the cycle stages of introduction, growth, maturity and shakeout against cash policies adopted by the company. This research is considered important because cash policy is influenced by company characteristics, namely the life cycle in which the determination of the company's life cycle is based on cash flow from operating, investing, and financing activities. This study uses panel data regression with a sample of the companies selected are manufacturing companies listed on the Indonesia Stock Exchange with an observation period from 2014-2019. By using a sample of 90 manufacturing companies, the results prove that the company has a large enough cash balance when the company is in the mature and shakeout cycle stages, while the introduction and growth cycle stages do not prove that the cash balance will be greater or less